Relationship Between Environmental Parameters and Manta Ray Occurrence in Raja Ampat Archipelago, Indonesia - Runtuboi, Ferawati; Bengen, Dietriech Geoffrey; Nurjaya, I Wayan; Natih, Nyoman Metta N; Zulfikar, Andi; Beale, Calvin S. (Marine Science Department Diponegoro University, 2024)
Understanding the influence and impact of environmental factors on manta ray sightings is critical to understanding the spatial and temporal ecology of a highly mobile species. Therefore, this study aims to determine the influence and impact of environmental factors as indicated by the parameters of wind speed, chlorophyll-a, SST, salinity, pH, dissolved oxygen, and the number of phytoplankton and zooplankton species. The mapped chlorophyll-a was re-analyzed based on the seasonal period throughout 2021 downloaded from marine copernicus and analyzed by kriging method. The influence and effects of environmental parameters on the short-term appearance of eye rays were studied using an adaptive model (GAM). The analysis showed a significant influence of environmental factors on manta ray sightings in Raja Ampat, namely Calanoid spp, Oithona nana, Acartia clausi, Calanus helgoladicus, and Oithona brevicornis. Based on this model, zooplankton is an important parameter that can describe the influence of environmental parameters on manta ray sightings at observation points in Raja Ampat MPA. The results of the reanalysis of chlorophyll-a concentrations were highest in the eastern to transitional seasons, which were scattered on the west side of Raja Ampat waters. Meanwhile, chlorophyll-a concentrations were low in the west to transitional season on the east side. This mechanism may drive the foraging strategy of manta rays, which visit shallow waters where zooplankton density and biomass are abundant. Adopting the BHS MPA network concept, as it has been implemented, would be in line with broader conservation expectations for the sustainability of manta rays in Raja Ampat.